Analisis Kemampuan Komposit Silika Slag Nikel dan Karbon Aktif untuk Menurunkan Kadar Fosfat - Fitria Eka Ilsa Putri (SAINS : Jurnal Kimia & Pendidikan Kimia, 2021)
Research has been carried out on the Analysis of the Ability of Silica Composites from Nickel Slag and Activated Carbon to Reduce Phosphate Levels. This study to determine the optimum mass of silica-activated carbon composite adsorbent and optimum pH of activated carbon composite adsorbent to reduce phosphate levels. The method used is quantitative analysis method. The optimized adsorption parameters were pH (3,4,5,6) and mass of composite adsorbent (0.05 g, 0.1 g, 0.2 g, 0.4 g). The results showed that the silica-activated carbon composite adsorbed phosphate at the optimum pH 4 with an adsorption efficiency of 89.18% and the optimum mass of the activated carbon-silica composite adsorbent was 0.05 grams. Thuse the silica-activated carbon composite can be used as an adsorbent to reduce phosphate levels.